Modelling, computation and optimization in information systems and management sciences : Second International Conference MCO 2008, Metz, France - Luxembourg,September 8-10, 2008 : proceedings - MCO 2008 (2008 : Metz, France); Le Thi, Hoai An; Pascal, Bouvry; Pham, Dinh Tao (Berlin : Springer, 2008)
28